Primary school leadership in Malaysia: The experience of stress among deputy heads. (September 2019) - Tahir, Lokman; Musah, Mohammed Borhandden; Panatik, Siti Aisyah; Ali, Mohd Fadzli; Said, Mohd Nihra Haruzuan Mohd
Unquestionably, studies focusing on school leaders' stress while managing schools have received extensive attention. However, there is still a lack of research focusing on deputies' stress, even though deputies play an essential role in a school's improvement process. Despite deputies' dual roles, it is an accepted fact that deputies do experience stress while simultaneously dealing with their 'superiors', fulfilling their administrative tasks and helping teachers to work at their fullest capacity. Based on these two noteworthy premises, this mixed-methods study was designed to explore and address whether dealing with educational superiors causes stress to primary deputies. Regarding the sample, 120 deputies from across 45 primary public schools in two urban districts were selected as respondents for the study. Regarding the quantitative data, the non-parametric and descriptive statistics were employed in determining deputies' views of their superiors. Further, eleven deputies were interviewed, and their anonymity was also protected to sustain the ethical considerations of the study. As expected, truculent attitudes and criticisms from school inspectors and parents were highlighted by deputies as contributing to their experiences of stress, with the levels of stress being classified as 'moderate' based on their demographic differences. Surprisingly, primary deputies revealed that they do not face much stress when working with their own head teachers; in fact, primary deputies informally revealed that their heads were quite open and understanding of their viewpoints and lenses.